2005
DOI: 10.2165/00003088-200544100-00006
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Mycophenolic Acid in Renal Transplant Recipients

Abstract: The developed population pharmacokinetic model adequately describes the pharmacokinetics of MPA in renal transplant recipients. The identified correlations appear to explain part of the observed inter- and intrapatient pharmacokinetic variability. The clinical consequences of the observed correlations remain to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 30 publications
9
70
1
2
Order By: Relevance
“…5,[14][15][16] In contrast, the average plasma half-life in liver and renal transplant patients is about 6 and 11 h, respectively. 17,18 For healthy adults half-lives of about 16-18 h were determined. 19,20 In consequence, similar MMF doses as used in SOT achieved lower AUC values in the range of 10-30 mg/ml h and C min levels o1 mg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…5,[14][15][16] In contrast, the average plasma half-life in liver and renal transplant patients is about 6 and 11 h, respectively. 17,18 For healthy adults half-lives of about 16-18 h were determined. 19,20 In consequence, similar MMF doses as used in SOT achieved lower AUC values in the range of 10-30 mg/ml h and C min levels o1 mg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…A more detailed description of the technical aspects of the methods that are used for pharmacokinetic modeling are reported elsewhere (unpublished observations, Van Hest et al, 2005). Briefly, during the first step of the analysis, a compartmental population pharmacokinetic model was developed describing the pharmacokinetics of MPA and quantifying between-and within-patient variability in MPA pharmacokinetics.…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
“…For example, some studies found that impaired renal function and low albumin levels result in high total MPA clearance and thus low total MPA exposure (5,9,11,13,14), although this could not be confirmed in all stud-ies (15)(16)(17)(18)(19)(20). Also with regard to the effect of the use of comedication (3,10,18,21,22), diabetes (23,24), body weight (11,13,17,20), age (5,11,18 -20), gender (11,20,23), and race (9,23,25), contrasting results have been obtained. Most of these studies were underpowered, based on MPA predose levels only, and some studies did not control adequately for confounding factors.…”
mentioning
confidence: 99%
“…With the use of population PK modeling and including the early posttransplantation period (days 3 to 140), major factors identified thus far that correlate significantly with MPA clearance include creatinine clearance, plasma albumin concentration, and CsA daily dosage (32). In a meta-analysis of longitudinal data in which MPA PK values were available from day 1 after transplantation out to 10 yr, it was estimated that kidney function, plasma albumin concentration, hemoglobin concentration, and CsA predose concentration could explain 18% of the between-patient and 38% of the within-patient variability in MPA exposure (29).…”
Section: Population Pk Modelsmentioning
confidence: 99%